Effectiveness of Mixed Clove Flower Extract (Syzygium Aromaticum) And Sweet Wood (Cinnamon Burmanni) on the Growth of Enterococcus Faecalis - Sarahfin Aslan; Masriadi; Nur Rahmah Hasanuddin; Andi Tenri Biba Mallombasang; Nur Azizah A.R (Indian Journal of Forensic Medicine & Toxicology, 2022)
Failed root canal treatment can cause problems such as recurring pain and leave persistent bacteria in the root canal. One of the bacteria that often causes root canal treatment failure is Enterococcus faecalis. The use of a root canal irrigation agent such as sodium hypochlorite (NaOCl) can help inhibit the growth of bacteria in the root canal. The use of materials derived from nature can be used as an alternative material for root canal irrigation because they inhibit growth and kill bacteria and have fewer side effects than chemicals. Several studies have tried to prove the use of ingredients of natural origin in the form of a mixture and the results obtained are higher when compared to single use. Natural ingredients that are often used as herbal medicine include cloves and cinnamon. Objective. To determine the effectiveness of a mixture of clove flower extract (Syzygium aromaticum) and cinnamon (Cinnamon burmanni) on the growth of Enterococcus faecalis. Methods. Using experimental laboratory methods, with a research design in the form of Post Test Only Control Design, sampling by random sampling using 5 treatments and 5 repetitions. Statistical test using One Way Anova. Results. This study showed the diameter of the inhibition zone of Enterococcus faecalis bacteria in a mixture of clove flower (Syzygium aromaticum) and cinnamon (Cinnamon burmanni) extract at 5% concentration of 10.84 ± 0.73, 10% concentration of 15.00 ± 0.80 mm. The concentration of 15% was 16.32 ± 1.04 mm and based on statistical tests obtained a significant value of P <0.01. Conclusion. The alternative hypothesis of this study is accepted and this study shows that there is an effectiveness of a mixture of clove flower extract (Syzygium aromaticum) and cinnamon (Cinnamon burmanni) concentrations of 5%, 10%, and 15% in inhibiting the growth of Enterococcus faecalis.